2010
DOI: 10.14411/eje.2010.039
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and phenotypic diversity of two northern populations of Cheilosia aff. longula (Diptera: Syrphidae) has implications for evolution and conservation

Abstract: Abstract. The genetic structure and phenotypic diversity of two populations of Cheilosia aff. longula (Diptera: Syrphidae) in Lapland, Finland, were examined using DNA sequencing, protein electrophoresis, and geometric morphometrics. The morphological identification of the species were verified using partial sequences of mitochondrial cytochrome c oxidase subunit I (COI mtDNA), and the nuclear ribosomal internal transcribed region 2 (ITS2 rDNA), and comparing the corresponding sequences of Cheilosia aff. longu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…By contrast to wing size, statistically significant sexual dimorphism based on wing shape was found in all studied populations of M. albifrons . Previous studies on several hoverfly taxa also showed statistically significant sexual shape dimorphism (Ludoški et al ., ; Milankov et al ., , 2010a, b; Francuski et al ., 2011b). The presence of significant differences in wing shape between females and males is an indication that the genetic part of the overall phenotypic variance is strongly involved (Monteiro et al ., ; Matta & Bitner‐Mathé, ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast to wing size, statistically significant sexual dimorphism based on wing shape was found in all studied populations of M. albifrons . Previous studies on several hoverfly taxa also showed statistically significant sexual shape dimorphism (Ludoški et al ., ; Milankov et al ., , 2010a, b; Francuski et al ., 2011b). The presence of significant differences in wing shape between females and males is an indication that the genetic part of the overall phenotypic variance is strongly involved (Monteiro et al ., ; Matta & Bitner‐Mathé, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, although geometric morphometric analysis using wing venation landmarks has been shown to be useful for distinguishing geographic conspecific populations in hoverflies, this method has been mainly applied to the study of genera with patchy distribution and species with non‐migratory behaviour, such as Cheilosia spp. (Ludoški et al ., ; Milankov et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Morphometric analysis of wing landmarks has been used to determine the variability in size of laboratory strains of flies and differences between natural populations (e.g. Milankov et al, 2010;Prudhomme et al, 2012). Measurements of differences in wing size (based on centroid size analysis) provide information that can be evaluated statistically and critically (Rohlf, 1993).…”
Section: Introductionmentioning
confidence: 99%